HUBUNGAN KECERDASAN INTERPERSONAL DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS V DI SDN 4 CURAH JERU KECAMATAN PANJI - Roviatul Adhewiyah; Amalia Risqi Puspitaningtyas (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2015)
Good education is an education that can explore all pupils’ potential. But not many schools have the capability; even, they do not know the other side of the potentials own by their pupil’s. Relate to the academic potential matter, the most visible potential based on the IQ measurement which is only optimizing three categorize: verbal ability (language), numeric (number ability) and visual spatial (ability to look the relation between space) .The formulation of problem in this research is there any significant relationship between the interpersonal intelligence and learning outcomes in subject Indonesian language, pupils grade V in public elementary school of SDN 4 Curah Jeru district of Panji. The aim of this research is to know is there any significant relationship between the interpersonal intelligence and learning outcomes in subject Indonesian language, pupils grade V in public elementary school of SDN 4 Curah Jeru district of Panji. The design of this research uses the plan of ex-post facto with the method of interviewing, documenting and questionnaire. The data analysis is using the analysis of quantitative research. After, researcher conducts the research and gathers the data; researcher is analyzing data from the result of pupil’s questionnaire analysis and pupil’s study outcomes then it is obtained Fcount of 0,967, while Ftable of 0,334 in N = 20 with significant level 5% it means that Fcount > Ftable meaning that null hypothesis (H0) is rejected and working hypothesis (Ha) is accepted. Based from the result it can be conclude there is a significant relationship between the interpersonal intelligence toward the learning outcomes in subject of Indonesian language, grade V semester 1 in public primary school of SDn 4 Curah Jeru academic year 2015/2016. Based on the result of the research and the discussion, it conclude that the success of pupil’s of public primary school in SDN 4 curah Jeru district of Panji academic year 2015/2016 grade V will be better if the interpersonal intelligence is higher. Therefore, the higher of interpersonal intelligence of the pupils the better of learning outcomes they will achieve. In contrast, the low of interpersonal intelligence, learning outcomes will be less